Pengaruh Penggunaan Ankle Foot Orthosis terhadap Kualitas Cara Berjalan pada Pasien Stroke - Nasyiatunnisa, Taqiyya; Sri Hidayati, Ari Budiati; Pratiwi, Yuni (MES Bogor, 2025)
Stroke is the main cause of motor disability, one of which is walking disorders due to hemiparesis. This study aims to determine the effect of using Ankle Foot Orthosis (AFO) on walking quality in non-hemorrhagic stroke patients. The method used is a case study on a 58-year-old female patient with left hemiparesis. The intervention in the form of using AFO was carried out for five consecutive days, once a day, with daily evaluation of walking quality using observation sheets and recording walking time of 5 meters. The results showed an improvement in walking after using AFO. On the first day before use, the patient walked draggingly and needed 27 seconds to cover a distance of 5 meters. After using AFO, there was an improvement in posture, stability, and lifting of the left leg when stepping. Walking time also continued to improve during the five days of intervention. In conclusion, the use of AFO in stroke patients in the acute phase can help improve walking quality significantly. This intervention is effective as part of early mobilization efforts to prevent further decline in function and increase patient independence.